Coupled micromorphological and stable isotope analysis of Quaternary calcrete development. Issue 2 (September 2015) - Adamson, Kathryn; Candy, Ian; Whitfield, Liz
Abstract : Pedogenic calcretes are widespread in arid and semi-arid regions. Using calcrete profiles from four river terraces of the Rio Alias in southeast Spain, this study explores the potential of using detailed micromorphological and stable isotopic analysis to more fully understand the impacts of Quaternary environmental change on calcrete development. The four profiles increase in carbonate complexity with progressive age, reflecting calcretisation over multiple glacial–interglacial cycles since MIS 9 (c. 300 ka). Calcrete profiles contain a mixture of Alpha (non-biogenic) and Beta (biogenic) microfabrics. Alpha fabrics have higher δ 13 C and δ 18 O values. The profiles contain a range of crystal textures, but there is little difference between the δ 13 C and δ 18 O values of spar, microspar, and micrite cements. Strong positive covariance between δ 13 C and δ 18 O suggests that both isotopes are responding to the same environmental parameter, which is inferred to be relative aridity. The study reveals that the detailed co-analysis of calcrete micromorphology and stable isotope signatures can allow patterns of calcrete formation to be placed into a wider palaeoclimatic context. This demonstrates the potential of this technique to more reliably constrain the palaeoenvironmental significance of secondary carbonates in dryland settings where other proxy records may be poorly preserved.